Organizational behavior : an experiential approach / Joyce S. Osland ... [et al.]. - Osland, Joyce (Upper Saddle River, N.J. : Pearson Education, 2007)
Reflecting the state of the art in the practice of experiential learning, Organizational Behavior: An Experiential Approach 8/e is teaching students general psychological principles and applying that knowledge to social and organizational situations. It teaches students to become continuous learners, capable of responding to demands for change and new skills throughout their career.
Psychological Contract & Commitment -- Theories of Managing People -- Individual and Organizational Learning -- Decoding Behavior -- Enhancing Motivation -- Values and Ethics -- Career Development and Work Stress -- Interpersonal Communication -- Perception and attribution -- Group Dynamics and Work Teams -- Problem Solving -- Creativity -- Conflict and Negotiation -- Managing Diversity -- Leadership -- Organizational Culture -- Decision Making -- Power and Influence -- Empowerment and Coaching -- Performance Management -- Organization Design -- Managing Change.
Rev. ed. of: Organizational behavior / Joyce S. Osland, David A. Kolb, Irwin M. Rubin. 7th ed. c2001.
Includes bibliographical references and index.
1
Keywords: EMBA; MOT; Psychology, Industrial; Organizational behavior